Sexual Harassment Among Chinese Psychiatrists and Its Impact on Quality of Life: A Cross-Sectional Survey - Xiao Y; Liu L; Chen TT; Zhang Z; Wu XH (Dove Medical Press, 2024)
Yu Xiao,1,2 Liang Liu,3 Ting-ting Chen,4 Zhou Zhang,5 Xiao-hong Wu6 1Psychosomatic Medical Center, The Fourth People's Hospital of Chengdu, Chengdu, Sichuan Province, 610036, People's Republic of China; 2Psychosomatic Medical Center, The Clinical Hospital of Chengdu Brain Science Institute, MOE Key Laboratory for Neuroinformation, University of Electronic Science and Technology of China, Chengdu, Sichuan Province, 610036, People's Republic of China; 3Department of Urology, Baoding No.1 Central Hospital, Baoding, Hebei Province, 071030, People's Republic of China; 4Mental Health Center, West China Hospital of Sichuan University, Chengdu, Sichuan Province, 610044, People's Republic of China; 5Department of Gastroenterology, Xiangyang No.1 People's Hospital, Hubei University of Medicine, Xiangyang, Hubei Province, 441011, People's Republic of China; 6Nursing Department, Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, Affiliate Cancer Hospital of University of Electronic Science and Technology of China, Chengdu, Sichuan Province, 610041, People's Republic of ChinaCorrespondence: Yu Xiao, The Fourth People's Hospital of Chengdu, No. 8, Huli West Lane 1, Yingmenkou Road, Chengdu, Sichuan Province, 610036, People's Republic of China, Tel +86-028-85641749, Email xiaoy3@outlook.comObjectives: Sexual harassment (SH) is a prevalent issue in various professional fields worldwide. The current study aims to investigate the incidence of SH targeting psychiatrists in China and explore its impact on quality of life (QOL).Methods: A consecutive recruitment of 1093 psychiatrists was conducted from 6 hospitals in China. The recorded data included participants' socio-demographic characteristics, experiences of workplace SH within the previous year, and their QOL. SH comprised verbal harassment, physical harassment, and displaying of sexual organs. The Chinese version of the World Health Organization Quality of Life Brief Version (WHOQOL-BREF) was employed to assess QOL. We compared the demographic characteristics and QOL between the SH group and the non-SH group. Multiple logistic regression analysis was used to identify independent demographic correlates of SH.Results: In total, 13.8% (n = 151) of the psychiatrists reported SH, with 5.8% reporting it once, 4.4% reporting it twice, and 3.6% reporting it three times or more. Psychiatrists who had encountered SH exhibited lower QOL across social, psychological, physical, and environmental domains. Multiple logistic regression analysis revealed that young physicians and those with shorter work experience had a higher likelihood of experiencing SH.Conclusion: The high prevalence of SH among Chinese psychiatrists is of concern. Given its detrimental effects on the well-being of physicians and the quality of medical care they provide, it is crucial to develop specialized employee training programs for this population to effectively manage workplace SH.Keywords: China, psychiatrists, quality of life, mental health professionals, sexual harassment, workplace safety